God in the Personalism of Borden Parker Bowne. - Jastrzębski, Andrzej (Filozofia Chrześcijańska, 2014)
This presentation examines B. P. Bowne’s view of God. God is an active and self-determining being. Nature is understood by Bowne as activated by the intellect and will of God. Bowne stated that each person has the attributes of awareness and self-awareness, freedom and the ability to act, and self-control – in a perfect way possessed only by God. Bowne’s theistic personalism shows the human person to be a spiritual being, ultimately deriving from God, the Most-High Person.